Diagnosis and Management of Radiation Necrosis in Patients With Brain Metastases - Vellayappan, Balamurugan; Tan, Char Loo; Yong, Clement; Khor, Lih Kin; Koh, Wee Yao; Yeo, Tseng Tsai; Detsky, Jay; Lo, Simon; Sahgal, Arjun (Frontiers in Oncology, 2018)
The use of radiotherapy, either in the form of stereotactic radiosurgery (SRS) or whole-brain radiotherapy(WBRT), remains the cornerstone for the treatment of brain metastases(BM). As the survival of patients with BM is being prolonged, due to improved systemic therapy (i.e. for better extra-cranial control) and increased use of SRS (i.e. for improved intra-cranial control), patients are clinically manifesting late effects of radiotherapy. One of these late effects is radiation necrosis(RN). Unfortunately, symptomatic RN is notoriously hard to diagnose and manage. The features of RN overlap considerably with tumor recurrence, and misdiagnosing RN as tumor recurrence may lead to deleterious treatment which may cause detrimental effects to the patient. In this review, we will explore the pathophysiology of RN, risk factors for its development, and the strategies to evaluate and manage RN.